Sex change and reproductive output of the protandric shrimp Merguia rhizophorae (Rathbun, 1900) (Decapoda, Merguiidae) - Alves, Douglas Fernandes Rodrigues; Barros-Alves, S. P.; Almeida, A. C.; Costa, R. C. [UNESP] (Taylor & Francis, 2021)
The aim of this study was to confirm the type of protandry adopted by M. rhizophorae and to describe the size at which sex change occurs in order to test predictions of sex allocation theory. The reproductive output also was investigated, based on fecundity and embryo volume. Specimens were collected cohabiting burrows built by mud shrimps Upogebia omissa in an estuary region in the northeast of Brazil. The body size (carapace length, CL) and sex of the shrimps were recorded. Observations were made developmental stages of the embryos, fecundity, and embryo volume. A total of 204 M. rhizophorae individuals was sampled, of which 170 (83.3%) male phase (MP) and 34 (16.7%) female phase (FP) individuals. The body size (mean ± SD) of the individuals in the MP was smaller than in the FP: 3.91 ± 0.78 and 6.18 ± 0.52 mm CL, respectively. The size at which 50% of the shrimps changed to FP (CL50) was 5.62 ± 0.01 mm CL. Reproductive output (fecundity and embryo volume) increased linearly with shrimp body size. An increase in embryo size during development and the loss of embryos during final stage of development were recorded. In this study, the behaviour exhibited by M. rhizophorae (share a burrow with another shrimp species) was recorded for the first time, expanding knowledge about the ecology of this semi-terrestrial shrimp. Our results indicate the adoption of strict protandric hermaphroditism by M. rhizophorae. Our study supports the prediction of sex allocation theory that sex ratio is significantly biased towards the first-sex in sequential hermaphrodites. We also found evidence of possible trade-offs between the size in which the sex change occurs and the reproductive strategy exhibited by M. rhizophorae.
Keywords: Hermaphroditism; k-strategy; protandry; reproductive investment; symbiosis